2010
DOI: 10.5650/jos.59.299
|View full text |Cite
|
Sign up to set email alerts
|

Physiological Functions of iso-type Short-Chain Fatty Acid and Omega 3 Polyunsaturated Fatty Acids Containing Oil in Obese OLETF Rats

Abstract: It has been known that tissues of porpoise contain unique structured-lipids as combination of isovaleric acid (iso-C5:0) and omega 3 polyunsaturated fatty acids (ω3 PUFAs). It is well known that ω3 PUFAs have lipid-lowering effects in animal and human studies. Although branched chain fatty acids have been interested in their unique functions, there is no data concerning the effect of iso-C5:0 on lipid metabolism. In this study we investigated the effect of structured-lipids from porpoise adipose tissue (porpoi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
0
2

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 43 publications
(39 reference statements)
1
9
0
2
Order By: Relevance
“…Fecal concentrations of both iso‐butyric and ‐valeric acid correlated negatively with blood levels of TG in our population, which is in line with two dietary intervention studies from the literature, one in rats using lipids from porpoise adipose tissue that contains substantial amounts of isovaleric acid and one in steers fed chromium . Both studies reported opposite associations between serum TG and isovaleric acid.…”
Section: Discussionsupporting
confidence: 88%
“…Fecal concentrations of both iso‐butyric and ‐valeric acid correlated negatively with blood levels of TG in our population, which is in line with two dietary intervention studies from the literature, one in rats using lipids from porpoise adipose tissue that contains substantial amounts of isovaleric acid and one in steers fed chromium . Both studies reported opposite associations between serum TG and isovaleric acid.…”
Section: Discussionsupporting
confidence: 88%
“…The inhibitory effect on PKB phosphorylation observed in response to the branched and non-branched SCFAs and the phosphorylation and inactivation of ACC 33 might be molecular mechanisms for diminished de novo lipogenesis. Isovaleric acid-containing porpoise oil, given in the diet, has ameliorating effects on fatty liver in OLETF (Otsuka Long- Evans Tokushima Fatty) rat, a model for type 2 diabetes, by increasing serum levels of adiponectin and enhancing lipoprotein synthesis and secretion 56 . However, isobutyric and isovaleric acid have been scarcely investigated with regard to effects on de novo lipogenesis.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies of Shirouchi and al. [47] suggested that feeding porpoise oil containing SLs as a combination of n-3 PUFAs and isovaleric acid (iso-C5:0), prevents the development of fatty liver disease through the enhancement of lipoprotein secretion and increase the adiponectin production in obese rats.…”
Section: Property Attributes Of Medium and Long Chain Triacylglycerolsmentioning
confidence: 99%